CHANGES IN THE MORPHOLOGY OF THE UZBEK LANGUAGE (International Conference on Economics, Finance, Banking and Management, 2025)
This article analyzes the main changes in the morphology of the Uzbek language. The changes are particularly noticeable in word formation, affixes, and the syntactic and semantic transformations of word classes. The historical development of morphology is also discussed. The article explores the influence of social and cultural factors on the language's development, including the emergence of new words, affixes, and syntactic structures.